Community Answer

The pdf is given by,{:[f(x;theta)=a(theta)b(x)e^(-[c(theta)d(x)],)","u <= x <= theta],[=0quad0.omega". "]:}The joint pdf of x_(1),dots,x_(n) is,f(x_;theta)=(a(theta))^(n)(prod_(i=1)^(n)b(x_(i)))e^(-[c(theta)sum_(i=1)^(n)d(x_(i))])Note that,{:[f(x^('),theta)=(a(theta))^(n)(prod_(i=1)^(n)b(x_(i)))e^(-sum_(i=1)^(n)[(theta)d(x_(i))])],[=(*(a(theta))^(n)e^(-c(theta)sum_(i=1)^(n)d(x_(i)))*(prod_(i=1)^(n)b(x_(i))):}],[=g(T;theta)*h(x)]:}where, T=sum_(i=1)^(n)d(x_(i)) and h(x_) hat(is)^(S)=prod_(i=1)^(n)b(x_(i)) which does not depend on the parameter ... See the full answer